2022-RA-1683-ESGO VTE in newly diagnosed ovarian cancer patients. (20th October 2022) - Shai, Daniel; Korach, Jacob; Helpman, Limor
Abstract : Introduction/Background: Ovarian cancer is commonly diagnosed at advanced stages, and is frequently treated with neoadjuvant chemotherapy. Advanced cancer patients are at risk for venous thromboembolism (VTE) and benefit has been shown using anticoagulants in risk stratified populations. Although a limited number of publications describe high rates of VTE among ovarian cancer patients, predictors of risk in this population have not been well studied. Our objective was to define rates of VTE among ovarian cancer patients receiving first-line chemotherapy and to identify predictors. Methodology: Ovarian cancer patients receiving first-line chemotherapy in Sheba Medical Center between 2013–2021 were identified, and data retrieved from the electronic medical record (EMR), institutional pharmacy records and imaging reports using dedicated software (MDClone©, Israel). A Natural Language Processing algorithm was created to identify VTE events to augment recorded diagnoses. Descriptive statistics were used to compare patients experiencing a VTE around and up to one year after beginning chemotherapy, to patients who did not. Logistic regression analysis was used to evaluate predictors of VTE. Results: 697 records were identified. VTE during the first year was diagnosed in 74 (10.6%), of whom 40 were DVT and 34 were PE. The majority were diagnosed in the first 6 months ( figure 1 ). Only 5 were diagnosed in the 30-day postoperative period. Patients with a VTE diagnosis were older (mean, 65.4 vs 62.3, p=0.03) and had lower albumin levels (mean, 3.08 vs 3.29, p=0.04). Other predictors of VTE on univariable regression analysis included poor performance status, neoadjuvant chemotherapy and a Khorana Score ≥ 2, but none were found to be independent predictors ( table 1 ). Conclusion: VTE is frequent in the first year, and particularly in the 6 months around ovarian cancer diagnosis. Risk may be predicted using established risk algorithms. Prophylactic anticoagulation may be considered in at-risk patients during first line chemotherapy.